Fluorescence lifetime evolution of crude oils during thermal cracking: Implications from pyrolysis experiments in a closed system. (September 2021) - Cheng, Peng; Liu, Botong; Tian, Hui; Xiao, Xianming; Gai, Haifeng; Zhou, Qin; Li, Tengfei; Liu, Dehan
Highlights: Oil fluorescence lifetime first increases and then decreases as oil cracking proceeds. Changes in aromatics type and concentration control oil fluorescence lifetimes. Oil cracking cannot mask the fluorescence lifetime differences of different oils. Fluorescence lifetime may be used to identify oil cracking extent and oil origin. Abstract: In this study, pyrolysis experiments were performed on two crude oils with different origins in a closed system, and the pyrolyzed oils were then analyzed for spectral parameters, including fluorescence lifetime, fluorescence spectra and infrared spectra, as well as for gross chemical compositions. The results show that the evolution of the fluorescence lifetime of crude oil (τoil ) can be divided approximately into two stages during oil cracking. With the increasing extent of oil cracking (PC ), the τoil first increases at the early cracking stage of PC  < 40%, and then it decreases at the late cracking stage of PC  > 40%. The type and concentration of aromatics in crude oils, which can be respectively characterized by the fluorescence lifetime of aromatics (τaro ) and the saturates/aromatics ratio (Rsat/aro ) of the oils, largely control the fluorescence quantum yield and fluorescence quenching degree of the oils, respectively, and thus the changes in the two factors during oil cracking determine the fluorescence lifetime evolution of crude oils. The differences in fluorescence lifetime of the crude oils that are sourced from diverse types of organic matter cannot be masked by the oil cracking process when the PC  is smaller than 80%. Combined with fluorescence or infrared spectral data, the fluorescence lifetime potentially can be applied to discriminate oils of various origins in petroleum reservoirs, especially in deep, light oil/condensate reservoirs where biomarker concentration is extremely low.